Mandated volunteering: an experimental approach. Issue 27 (9th June 2018) - McCarty, Sara Helms; Angner, Erik; Scott, Brian; Culver, Sarah
ABSTRACT: This study employs a novel experimental paradigm to examine crowdout effects in volunteering. Using a framework modelled upon money donation experiments, we examine the impact of 'forced' volunteering on the amount of time volunteered. We find that subjects exposed to forced volunteering on the mean voluntarily donate less time than subjects in the control condition. Among religious subjects, the crowdout is 52.8%, suggesting warm-glow giving. Among non-religious subjects, the crowdout is 138%, implying altruistic giving. Thus, policies mandating volunteer activity may be associated with sizeable crowdout effects and might have heterogeneous effects across subpopulations.